Radiation Oncology in Palliative Cancer Care - Lutz, Stephen; Chow, Edward; Hoskin, Peter J. (New York : Wiley, 2013)
Radiation Oncology in Palliative Cancer Care represents the first dedicated attempt in book form to address the glaring absence of a well-written palliative radiation therapy reference and textbook that provides a template for the end-of-life care of patients who require intervention by Radiation Oncologists as well as Hospice and Palliative Medicine Professionals working together. Palliative radiotherapy will gain increasing importance in the provision of end-of-life care for cancer patients in the coming years, and there is an immediate need for an instructive reference and textbook to guide.
Palliative radiation and hospice.
Includes bibliographical references and index.
Print version record.
Keywords: Cancer -- Radiotherapy; Palliative treatment; Neoplasms -- radiotherapy; Palliative Care -- methods; Radiation Oncology -- methods; Radiotherapy -- methods; HEALTH & FITNESS -- Diseases -- Cancer; MEDICAL -- Oncology; Cancer -- Radiotherapy; Palliative treatment; Electronic books